Modeling and control of dynamic battery storage system used in hybrid grid. Issue 3 (9th March 2020) - Sarita, Kumari; Devarapalli, Ramesh; Rai, Pankaj
Abstract: In renewable energy‐based grids, the most challenging tasks are to achieve uninterrupted, reliable, and continuous power supply from these grids. From literature, the problems in these grids and their associated solutions are (a) discrepancy between generation and demand: this is resolved by hybrid solar‐wind battery storage system (BSS), (b) requirement of improved efficiency and reliability: this is achieved by the use of state‐of‐the‐art controllers and innovative switching systems, (c) analysis of dynamic systems, optimization, and control: for these, mathematical modeling of systems is prepared, which is a tough task as solar, wind, and battery system contain nonlinear parameters. This article focuses on modeling and simulation of the wind turbine, photovoltaic (PV) arrays, and dynamic BSS. Moreover, control of variable speed wind turbines with pitch angle control, output power improvement of PV systems, and State‐of‐Charge (SoC) estimation of BSS with its characteristics parameters, temperature effects are analyzed in this work. The dynamic controller is provided which controls the charging/discharging of battery with the change in load, the power output of wind and solar system and makes the system reliable and efficient. In the result section, comparison of battery voltage and SoC is made by considering and neglecting the temperature effect.